The marine fauna of New Zealand : Leptothecata (Cnidaria Hydrozoa) (Thecate hydroids) - Vervoort, Willeim; Watson, Jeanette E. (NIWA (National Institute of Water and Atmospheric Research), 2003)
NIWA Biodiversity Memoir #115